1963
DOI: 10.1346/ccmn.1963.0120107
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Dehydration and Recrystallization of Serpentine—I

Abstract: Dehydration and recrystallization reactions of fine and coarse powders and also of massive samples of serpentine under isothermal heating conditions in air are followed by thermobalance measurements and by X-ray diffraction intensities. The rate of recrystallization to forsterite is shown to have an inverse relationship to the rate of dehydration. This result is interpreted in terms of the damage inflicted on the crystal structure of serpentine by the dehydration reaction; the more slowly this reaction occurs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Brindley and Hayami 1963). Comparison of the CI-like chondrites with mineral textures in artificially heated Murchison CM chondrite suggests that the metamorphism of Y-82162 and Y-980115 occurred over hours to several years (Nakato et al 2008).…”
Section: Thermal Metamorphism Of Ci-like Chondritesmentioning
confidence: 97%
“…Brindley and Hayami 1963). Comparison of the CI-like chondrites with mineral textures in artificially heated Murchison CM chondrite suggests that the metamorphism of Y-82162 and Y-980115 occurred over hours to several years (Nakato et al 2008).…”
Section: Thermal Metamorphism Of Ci-like Chondritesmentioning
confidence: 97%
“…[55][56][57][58][59] The proposed mechanisms, as shown in Figure 3, are based on a topotactic transition whereby forsterite and enstatite form from the Mg-rich and Si-rich regions, respectively. Based on their NMR results, MacKenzie and Meinhold 58,60 ( Figure 3d) updated the mechanism of Brindley and Hayami 56 ( Figure 3b) …”
Section: Thermal Reaction Sequencementioning
confidence: 99%
“…The large jump in frequency of the A 1g mode of lizardite down to 183 cm -1 and the jump in frequency of the s Si-O b -Si band is assigned to product phase(s) of the dehydroxylation. Under ambient, dry conditions the first recognizable dehydroxylation product is mainly amorphous, but crystallizes upon further heating to forsterite, followed by enstatite (Brindley and Hayami 1963). The stable products of the dehydroxylation reaction of pure magnesian lizardite under hydrothermal conditions are talc, forsterite, and water (O'Hanley et al 1989).…”
Section: Dehydroxylation Products: a Talc-like Intermediate And Forstmentioning
confidence: 99%
“…Various authors (e.g., McKelvy et al 2004;Brindley and Zussman 1957) reported low-angle peaks in X-ray diffractograms of thermally treated serpentine phases, indicating that amorphization is not complete and that dehydroxylation produces intermediate partially ordered structures. Although differing in detail, early studies by Ball and Taylor (1963) and Brindley and Hayami (1965) proposed reaction sequences with disordered dehydroxylated intermediates. They infer the presence of a partially ordered structure from the topotactic relationship between forsterite and serpentine (Brindley and Hayami 1963).…”
Section: Dehydroxylation Products: a Talc-like Intermediate And Forstmentioning
confidence: 99%
See 1 more Smart Citation